ENVIRONMENTAL HEALTH PROFILE AND ITS INFLUENCE ON THE PREVALENCE OF ENVIRONMENTALLY BASED DISEASES IN CIPANAS DISTRICT, CIANJUR, WEST JAVA, INDONESIA, IN 2022 - Eddy Siswanto; Agus Setiabudi (Bajang Institute, 2023)
A quantitative descriptive study by using secondary cross-sectional data from environmental health activity reports carried out by the Cipanas Community Health Center during 2022 describe the environmental health situation and conditions in Cipanas sub-district, Cianjur regency, West Java, Indonesia, are in good condition. There are 91% drinking water facilities that meet health requirements, 89.07 residents can access them sustainably, all residents in Cipanas District use healthy latrines, and all villages have community-based total sanitation. Around 78.87% of public places meet health requirements, and of 120 food processing places, only around 72.58% meet sanitation hygiene requirements, There are 86.43% classified as healthy houses, around 90.43% of houses in Cipanas sub-district have waste water drainage channels, 84.19% of all rubbish dumps are closed rubbish bins. Even though of the 5.07% of drinking water facilities inspected, around 88.58% had low-medium risk, and of the 0.28% of water samples taken, still around 29.58% met health requirements. Meanwhile, there are 3 environmental-based diseases that are mostly suffered by residents in Cipanas, namely ISPA/Pneumonia, Diarrhea and Skin Diseases. By using The Fisher Exact Test, it turns out that only the conditions of food processing places have a significant relationship with the incidence of environmental-based diseases (p = 0.0036). Meanwhile, there were other factors that are likely to influence the incidence of environmental-based diseases in Cipanas, including behavior that was not examined in this study. further studies need to be carried out regarding environmental health, especially clean and healthy living behavior so that it can become useful input for planning and implementing health programs in Cipanas sub-district